PENGARUH CELEBRITY ENDORSEMENT, BRAND IMAGE, DAN TESTIMONI TERHADAP MINAT BELI KONSUMEN PRODUK MIE INSTAN LEMONILO PADA MEDIA SOSIAL INSTAGRAM - Zahra Dhaefina; Merza Nur AR; Pirmansyah Pirmansyah; Vicky F Sanjaya (JURNAL MANAJEMEN, 2021)
The purpose of this study was to determine how much influence celebrity endorsement, brand image, and testimonials have on consumer buying interest in Lemonilo instant noodle products on social media Instagram. The method used in this research is by distributing online questionnaires. The sample of this study is 62 respondents, namely people who have consumed Lemonilo instant noodles, following at least one celebrity endorsement on Instagram and knowing the Lemonilo instant noodle brand. The results showed that the brand image variable had a significant positive effect on consumer buying interest on Instagram social media, while the celebrity endorsement and testimony variables had a positive effect on consumer purchase interest on Instagram social media. These results indicate that people are more concerned with brands when buying noodles for consumption.